2018
DOI: 10.15407/agrisp5.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on vibrational digging-up of sugar beet

Abstract: The technological process of vibrational digging-up of sugar beet has spread in many sugar beet-sowing coun- tries. The experience of using this process demonstrated its advantages compared against other ways of dig- ging-up, but there have been scarce experimental researches of the vibrational digging-up of sugar beet from soil which makes this topic urgent for sugar beet production. Aim. The experimental determination of rational parameters and modes of the vibrational digging-up working tool to ensure the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In [8] studies of the influence of the speed of the movement upon the drive power of a machine with vibrating digging tools were carried out, but this was done without changing the parameters of the vibration process and disclosing the reasons for changing the traction resistance. Also, much attention is paid to determination of the loss of the root crops after the passage of the beet-digging machine, depending on the speed of its movement; but at a constant frequency and amplitude of oscillations of the working tool with increasing speed we will get a decrease in the time and number of interactions of the working tool with the body of the root crop, which is not desired.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8] studies of the influence of the speed of the movement upon the drive power of a machine with vibrating digging tools were carried out, but this was done without changing the parameters of the vibration process and disclosing the reasons for changing the traction resistance. Also, much attention is paid to determination of the loss of the root crops after the passage of the beet-digging machine, depending on the speed of its movement; but at a constant frequency and amplitude of oscillations of the working tool with increasing speed we will get a decrease in the time and number of interactions of the working tool with the body of the root crop, which is not desired.…”
Section: Resultsmentioning
confidence: 99%
“…However, as practice has shown, the use of exactly the direction of vibration of the digging tools in a transverse-horizontal plane does not provide the necessary conditions for productivity and quality, which made it necessary to completely eliminate such oscillations. The following numerous theoretical and experimental investigations and design developments have shown that only the creation of oscillatory impacts upon the beet root bodies, which are in the soil exactly in a longitudinal-vertical plane, is the only possible way to further improvement of this technological process [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…where φ(x) -the proper form of the main vibrations; p -the proper frequency of the main vibrations. By substituting expression (12) into functional (11), we obtain:…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…The existing digging bodies for root crops, operating in a wide variety of conditions (different hardness moisture of the soil surrounding the root crops, non-straightness of the crop rows, etc. ), are not always able to fulfil the specified requirements, which leads to significant losses of the grown crop [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation